Higher dose weekly fluoxetine in hemodialysis patients: A case series report. (January 2021) - Kauffman, Kelley M; Dolata, Jacqueline; Figueroa, Maria; Gunzler, Douglas; Huml, Anne; Pencak, Julie; Sehgal, Ashwini R; Sajatovic, Martha
Objective: The antidepressant medication fluoxetine at 90 mg dosed weekly is as effective and safe as standard formulation fluoxetine 20 mg dosed daily in patients with major depressive disorder. Weekly fluoxetine has not been well studied in hemodialysis patients, and doses beyond 90 mg/week have not been described in this population. This case series, derived from a larger study on depression in hemodialysis patients, describes the use of weekly fluoxetine at dosages beyond 90 mg/week. Method: Hemodialysis patients with depressive symptom severity scored ≥10 on the 9-item Patient Health Questionnaire and major depressive disorder confirmed with Mini International Neuropsychiatric Interview were initially prescribed daily fluoxetine for two weeks and then transitioned to weekly fluoxetine. Dosage titration was made at the discretion of the prescribing clinician. Fluoxetine was continued for a total of 12 weeks. Results: Four women, aged 24 to 65 years, on hemodialysis for 1 to 18 years, were started on weekly fluoxetine that was increased over several weeks up to 180 mg. Side effects included restlessness, dry mouth, sedation, and lightheadedness. Two patients ultimately had their weekly fluoxetine decreased back to 90 mg. However, all four continued weekly fluoxetine as part of poststudy aftercare and no longer met diagnostic criteria for major depressive disorder, current episode. Conclusions: Weekly fluoxetine at doses of 180 mg may be a reasonable treatment consideration for hemodialysis patients who have partial or insufficient antidepressant response. Side effects may limit tolerance of the 180 mg dose in some individuals. Future research should investigate longer term health outcomes of weekly fluoxetine in this population.